Neglected reverse Essex-Lopresti injury with ulnar nerve - Singh Ajay Pal; Dhammi Ish Kumar; Jain Anil Kumar (Chinese Journal of Traumatology, 2011)
【Abstract】A 45 year old woman was diagnosed as having anteromedial radial head dislocation and distal radius fracture five months after her injury on right forearm. The radial head dislocation led to ulnar nerve compression. She had severe restriction of her elbow movements. She was treated with arthrolysis, decompression of the ulnar nerve and radial head resection. The reverse Essex Lopresti injury and radial head dislocation compressing the ulnar nerve has not been reported in English language literature to the best of our knowledge. A mechanism is proposed for the injury. In acute presentations, restoration of both the radioulnar joints should be done and neglected nature of such injury leads to suboptimal outcomes. Key words: Radius fracture; Unar nerve; Elbow joint